Multimodal imaging of micron‐sized iron oxide particles following in vitro and in vivo uptake by stem cells: down to the nanometer scale. (22nd April 2014) - Roose, Dimitri; Leroux, Frederic; De Vocht, Nathalie; Guglielmetti, Caroline; Pintelon, Isabel; Adriaensen, Dirk; Ponsaerts, Peter; Van der Linden, Annemie; Bals, Sara
<x xml:space="preserve">Abstract</x> In this study, the interaction between cells and micron‐sized paramagnetic iron oxide (MPIO) particles was investigated by characterizing MPIO in their original state, and after cellular uptake in vitro as well as in vivo. Moreover, MPIO in the olfactory bulb were studied 9 months after injection. Using various imaging techniques, cell–MPIO interactions were investigated with increasing spatial resolution. Live cell confocal microscopy demonstrated that MPIO co‐localize with lysosomes after in vitro cellular uptake. In more detail, a membrane surrounding the MPIO was observed by high‐angle annular dark‐field scanning transmission electron microscopy (HAADF‐STEM). Following MPIO uptake in vivo, the same cell–MPIO interaction was observed by HAADF‐STEM in the subventricular zone at 1 week and in the olfactory bulb at 9 months after MPIO injection. These findings provide proof for the current hypothesis that MPIO are internalized by the cell through endocytosis. The results also show MPIO are not biodegradable, even after 9 months in the brain. Moreover, they show the possibility of HAADF‐STEM generating information on the labeled cell as well as on the MPIO. In summary, the methodology presented here provides a systematic route to investigate the interaction between cells and nanoparticles from the micrometer level down to the nanometer level and beyond. Copyright © 2014 John Wiley & Sons, Ltd.